2007
DOI: 10.1002/jts.20271
|View full text |Cite
|
Sign up to set email alerts
|

Psychometric analysis and refinement of the connor–davidson resilience scale (CD‐RISC): Validation of a 10‐item measure of resilience

Abstract: Resilience refers to an individual's ability to thrive despite adversity. The current study examined the psychometric properties of the Connor-Davidson Resilience Scale (CD-RISC). Three undergraduate samples (ns < 500) were used to determine the factor structure of the CD-RISC. The first two samples were used to conduct exploratory factor analysis (EFA), and the third was used for confirmatory factor analysis. The EFA showed that the CD-RISC had an unstable factor structure across two demographically equivalen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

71
1,811
10
62

Year Published

2013
2013
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 2,303 publications
(2,071 citation statements)
references
References 25 publications
71
1,811
10
62
Order By: Relevance
“…The Connor-Davidson Resilience Scale 10 (CD-RISC 10) which measures degree of resilient coping in response to life challenges. 15 Research has shown that the CD-RISC 10 has an acceptable a coefficient of 0.85. 15 The Depression, Anxiety and Stress Scale (DASS-21), 16 as a screen of depressive mood, anxiety and stress.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The Connor-Davidson Resilience Scale 10 (CD-RISC 10) which measures degree of resilient coping in response to life challenges. 15 Research has shown that the CD-RISC 10 has an acceptable a coefficient of 0.85. 15 The Depression, Anxiety and Stress Scale (DASS-21), 16 as a screen of depressive mood, anxiety and stress.…”
Section: Methodsmentioning
confidence: 99%
“…15 Research has shown that the CD-RISC 10 has an acceptable a coefficient of 0.85. 15 The Depression, Anxiety and Stress Scale (DASS-21), 16 as a screen of depressive mood, anxiety and stress. The DASS-21 has shown sensitivity in detecting symptoms of depression and anxiety in SCI samples.…”
Section: Methodsmentioning
confidence: 99%
“…Campbell-Sills and Stein (2007) states that, in the psychology literature there is a consensus on the reliability and validity of the Conner-Davidson measure. In organizational theory literature, there are attempts to analyze the construct with different dimensions.…”
Section: Literature Reviewmentioning
confidence: 99%
“…A self-report Connor-Davidson Resilience Scale (CD-RISC) (Connor & Davidson, 2003) suitable for use with older adolescents in the context of education (Campbell-Sills & Stein, 2007;Singh & Yu, 2010) was completed by inductees. The CD-RISC is used to calculate total resilience (0-100) and five contributory subscale scores of (i) First which is the highest.…”
Section: Stagementioning
confidence: 99%